Selective degradation of chemical bonds from single-source molecular precursors to metallic Ag and semiconducting Ag2S nanocrystals via instant thermal activation - Tang, Qun (Langmuir : the ACS journal of surfaces and colloids, 2006)
Selective formation of metallic Ag and semiconducting Ag(2)S nanocrystals has been achieved via a modified hot-injection process from a single-source precursor molecule, Ag(SCOPh), which can potentially generate both [Ag] and [AgS] fragments simultaneously. When the precursor molecules are injected into a preheated reaction system at 160 degrees C, spherical Ag(2)S nanocrystals are directly obtained even without a molecular activator, such as alkylamines. Mixtures of Ag and Ag(2)S or pure metallic Ag nanocrystals are obtained if the precursor molecules are injected at lower than 160 degrees C or room temperature. These results are attributed to the direct transfer of thermal energies to precursor molecules, which are enough to dissociate S-C as well as Ag-S bonds simultaneously. Detailed characterizations about the produced nanocrystals have been performed using powder X-ray diffraction (XRD), transmission electron microscopy (TEM), as well as energy-dispersive X-ray (EDX) spectrum